Politics Without Television: The Bahujan Samaj Party and the Dalit Counter-Public Sphere - Loynd, Maxine (Television in India: Satellites, Politics and Cultural Change, 2008)
The place of the media in an effective liberal democracy is generally seen assacrosanct. The media play an important role in the collection and dissemination of information and provide an avenue for keeping politiciansaccountable to their constituents.Mindful of the impact themedia can have onthe fortunes of a political party, and the careers of individuals within it, mostpoliticians in liberal democracies tend to tread carefully in terms of how theymanage their relationship with the media. Politicians hire public relations andmedia advisors, and seek media training in order to learn how to ‘use’ themedia to further their political aims. In the main, the approach of India’spolitical parties to media relations has become remarkably similar. However, an exception appears when we examine the relationship of theBahujan Samaj Party (BSP), and its leader Mayawati, with the media in bothits mainstream forms – print and television. Despite early attempts to engagewith the media, by the late 1990s the BSP was running election campaignswith a media strategy of almost complete disengagement. This has not led topoor electoral results for the party. In fact, the party has been in power in thenorth Indian state of Uttar Pradesh (UP) on a number of occasions: in 1995,1997 and 2002, either in coalition or as a minority government. Upon winning minority government in the 2002 election, a journalist declared that ‘Inan age of television and information technology, Mayawati is a politician whodefies all conventional standards and norms . . . [and] despises giving interviews . . . ’(Bhushan, 2002: 18). In May 2007 the BSP won the UP state election outright to take power as the first majority government that UP hasseen for 15 years. Again this election was won while largely ignoring main-stream newspapers and television, with Mayawati even taunting journalistsafter the win, ‘I know you were upset I did not meet you during the campaign but I noticed that you had already run ahead with your conclusions, so Ithought why disturb you?’ (Gopinath, 2007).
Num Pages: 25
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Inde (corpus analysé); _Nettoyé